Barron's how to prepare for the TOEIC bridge test : - Lougheed, Lin (Tổng hợp Thành phố Hồ Chí Minh, 2005)
The TOEIC Bridge test is an English proficiency exam designed for programs set up to train beginning and intermediate students of the English language. This brand-new man-ual has been designed specifically for those language learners. It is suitable for use by high-school and college-level students, for immigrant language-training programs, and for learners in the workplace. The TOEIC Bridge test is a 100-question multiple-choice test divided into two sections: listening and reading.